Variação morfométrica e citogenética em Kerodon rupestris (Wied, 1820) (Rodentia: Caviidae) - Giúdice, Gisele Mendes Lessa del (2004)
Kerodon rupestris Wied, 1820) is a specie of caviídeo bearer of great corporal proportions and considered a habitat specialist inside of the group. Since the Pleistocene this specie has had its space distribution restricted to the Brazilian semi-arid area where is confined to rock islands. Three methodological approaches were adopted to define this pattern: 1) a sexual and cranial qualitative morfometric variability analysis inside of a recent population and a sub-fossil that later on was complemented by 2) a geographical analysis, also based on cranial characters, of nine recent populations spread along the geographical distribution of the specie, besides the population of sub-fossils and a population of K. acrobat; and 3) a comparative karyotype analysis among three populations of K. rupestris. The morphological and karyotypes evidences suggest that: a) a significant geographical variation takes place; b) morphologically, the sub-fossils specimens present cranial medium values larger than the recent individuals at the same age; c) a clinal increment variation of cranial dimensions in geographical north-south direction, among the populations of K. rupestris studied occur; d) there is a complete discrimination in the population of K. acrobat in the multivariate space of the cranial morphologic characters, not putting upon to the cline found in K. rupestris; e) there are two chromosomic forms for K. rupestris manifested by the differences obtained in the number and in the chromosomal morphology; f) there is a similarity for C-Band among the three populations of K. rupestris appraised; g) the Botumirim population in the southern of K. rupestris distribution is bearer of the karyotype, so far known, closer of the locality type defined by WIED 1820); and h) the morphological and karyotypes characteristics of the specimens from Botumirim (MG) differ from other populations of K. rupestris studied. To elucidate these differences found, an indicative of a complexity variation, it will be necessary new analyses, with a larger number of populations of K. rupestris along its geographical distribution.